Effects of Chronic Administration of P-Cymene in an Animal Model of LPS-Induced Autism - de Camargo, Rick Wilhiam; da Silva, Marina Goulart; Daros, Guilherme Cabreira; de Medeiros, Fabiana Durante; da Rosa, Naiana; Menschhein Medeiros, Caroline Liana; de Medeiros Peretti, Eduardo; Palandi, Juliete; Bobinski, Franciane; Fortunato, Jucélia Jeremias; de Bitencourt, Rafael Mariano (Planta Medica International Open, 2021)
p-Cymene is a monoterpene found in over 100 plant species. It shows a range of biological activity, including anti-inflammatory and antimicrobial effects. It is possibly a new therapeutic alternative for autism spectrum disorder characterized by deficits in interaction and behavioral abnormalities. These symptoms can occur in response to maternal immune activation through prenatal exposure to lipopolysaccharide. Thus, this study aimed to evaluate the behavioral, memory, and biochemical effects of chronic administration of p-cymene in an animal model of autism by prenatal maternal exposure to lipopolysaccharide. Twenty-four pregnant Wistar rats were used, who received 100 μg/kg of lipopolysaccharide or saline intraperitoneally (i.p.) on the 9.5 gestational day. After birth, the male offspring remained with the mothers until weaning and underwent model validation tests on postnatal day 30. From postnatal day 31 on, chronic administration, via i.p., of saline (1 mL/kg), risperidone (0.2 mg/kg), or p-cymene (100 mg/kg) for 22 days was performed. The animals were submitted to behavioral (postnatal day 52) and memory tests (postnatal days 52–53) and subsequently sacrificed (postnatal day 54) when their brain structures were removed for quantification of proinflammatory cytokines (TNF-α, interleukin 1β, and interleukin 6). Prenatal exposure to lipopolysaccharide significantly increased episodes of stereotyped movement (p=0.0001) and decreased parameters of social interaction in offspring, including sniffing, following, mounting, and allowing mounting (p=0.0043, p<0.0001, p=0.0009, and p=0.0200, respectively). Chronic p-cymene treatment was not significant for behavioral, memory, and biochemical tests. However, due to their pharmacokinetic characteristics, p-cymene nanomaterials’ formulation may be an exciting alternative to be tested for further results.
Keywords: p-cymene; maternal immune activation; autism spectrum disorder; lipopolysaccharides; proinflammatory cytokines